Clinical case of surgical treatment of undifferentiated pleomorphic liver sarcoma - Bakunets, Y. P.; Bakunets, P. P.; Zagriychuk, M. S.; Bryndak, I. A.; Samokishchuk, R. A.; Prytkov, F. O.; Korshunova, M. I. (General Surgery, 2025)
Undifferentiated pleomorphic liver sarcoma (UPS), formerly known as malignant fibrous histiocytoma (MFH), represents a very rare primary hepatic tumour. It was first described by O’Brien and Stout in 1964. This type of tumour is the most prevalent malignant soft tissue tumour, which usually occurs in adulthood and affects the extremities, less commonly the retroperitoneum and abdominal organs. Objective – to present the treatment outcomes of a rare case of UPS of the liver. The article describes a clinical case of surgical treatment of a patient with UPS of the liver. Patient N., 36 years old, complained of pain in the right hypochondrium, fever, and general weakness. According to the results of instrumental examinations, the clinical diagnosis was made: primary liver tumour, tumour rupture, and intra‑abdominal bleeding. After preoperative preparation, a right‑sided hemihepatectomy, D2 lymphadenectomy, cholecystectomy, and abdominal drainage were performed. The histopathological and immunohistochemical features of the tumour cells were most consistent with undifferentiated pleomorphic liver sarcoma. According to the Federation Nationale des Centres de Lutte Contre le Cancer (FNCLCC) sarcoma grading system, a total score of 7 (G3) was assigned. The diagnosis was undifferentiated pleomorphic liver sarcoma, pT4aN0M0 G3 stage III, grade 2. Six months later, a CT scan of the abdominal cavity revealed a tumour focus in the right subdiaphragmatic space with invasion of the right diaphragm dome, liver segment IV, and right kidney. Surgical intervention was performed in volume: viscerolysis, atypical resection of the SgIV liver with right‑sided nephrectomy and resection of the right dome of the diaphragm, aortocaval lymphadissection. Postoperative diagnosis: undifferentiated pleomorphic liver sarcoma rpT4N1(1/2)M0 G3, R0, stage III, grade 2. Currently, the period of recurrence‑free observation is 12 months after the second surgery.